2023
DOI: 10.3389/fphar.2023.1093017
|View full text |Cite
|
Sign up to set email alerts
|

Feiyiliu Mixture sensitizes EGFRDel19/T790M/C797S mutant non-small cell lung cancer to osimertinib by attenuating the PRC1/Wnt/EGFR pathway

Abstract: Introduction: Osimertinib is a potent epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) for the treatment of patients with EGFR-mutant non-small cell lung cancer (NSCLC). However, the emergence of acquired resistance due to the EGFR-Del19/T790M/C797S mutation limits the clinical application of osimertinib. Feiyiliu Mixture (FYLM), a clinical experience formula of Chinese medicine, was used to treat lung cancer with good clinical efficacy. In this study, we aimed to investigate the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…This is consistent with Reguart et al 32 and Ye et al 33 who reported that after 1-2 years, patients will inevitably develop resistance to EGFR-TKIs, resulting in secondary T790M mutation. With the increase of EGFR drug resistance, for example, the third generation TKI osimertinib is selective to activation mutation and T790M drug resistance, and the patient may have a mutation of C797S after 9-13 months' of treatment, and at present, there is no treatment for the drug resistance mediated by the triple mutation of 19Del/T790M/C797S, so it is necessary to further study the drug resistance mechanism of EGFR mutation and nd new targeted drug therapy [34][35][36][37] ; Therefor, more TKIs are approved to enter the clinic by FAD, which increases the economic pressure and drug toxicity of patients, such as zhu et al whose results showed that serious adverse events (SAE) induced by two different strategies of targeted therapy is 60% and 28% respectively 16 . Certainly, the solution to TKIs drug resistance is gradually being overcome, and EGFR is targeted through allosteric mechanism to overcome the drug resistance in ATP binding sites 38 ; A new class of EGFR PROTACs degrading agent based on pomalidomide was developed by O. Aboelez et al, which has good activity on both wild-type and mutant EGFR, and its anti-tumor cell proliferation effect has been con rmed in lung cancer cells in vitro 39 .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with Reguart et al 32 and Ye et al 33 who reported that after 1-2 years, patients will inevitably develop resistance to EGFR-TKIs, resulting in secondary T790M mutation. With the increase of EGFR drug resistance, for example, the third generation TKI osimertinib is selective to activation mutation and T790M drug resistance, and the patient may have a mutation of C797S after 9-13 months' of treatment, and at present, there is no treatment for the drug resistance mediated by the triple mutation of 19Del/T790M/C797S, so it is necessary to further study the drug resistance mechanism of EGFR mutation and nd new targeted drug therapy [34][35][36][37] ; Therefor, more TKIs are approved to enter the clinic by FAD, which increases the economic pressure and drug toxicity of patients, such as zhu et al whose results showed that serious adverse events (SAE) induced by two different strategies of targeted therapy is 60% and 28% respectively 16 . Certainly, the solution to TKIs drug resistance is gradually being overcome, and EGFR is targeted through allosteric mechanism to overcome the drug resistance in ATP binding sites 38 ; A new class of EGFR PROTACs degrading agent based on pomalidomide was developed by O. Aboelez et al, which has good activity on both wild-type and mutant EGFR, and its anti-tumor cell proliferation effect has been con rmed in lung cancer cells in vitro 39 .…”
Section: Discussionmentioning
confidence: 99%
“…YYD inhibited the proliferation of NSCLC cells by inhibiting the EGFR-PI3K-AKT signaling pathway [ 108 ]. Feiyiliu Mixture could reduce the phosphorylation of EGFR and down-regulate the expression of cyclin, and up-regulate the level of cleaved Caspase-3 protein to promote cell apoptosis [ 109 ]. Therefore, lung cancer treatment should consider modulating intestinal function as well.…”
Section: Regulation Of Lung and Intestinal Micro-immune Ecology Inhib...mentioning
confidence: 99%
“…Moreover, osimertinib is a third-generation powerful EGFR-TKI used to treat NSCLC patients with EGFR mutations. The therapeutic use of osimertinib is nonetheless restricted by the emergence of acquired resistance associated with the triple mutation Del19/T790M/C797S in EGFR [63]. Furthermore, mutations at either V550 (a gatekeeper residue) or C552 (hinge-1 residue) in the kinase domain of fibroblast growth factor receptor 4 (FGFR4) prevent fisogatinib (a potent and selective FGFR4 inhibitor) from interacting with the FGFR4's ATP binding site, resulting in acquired clinical resistance to fisogatinib in patients with HCC [64].…”
Section: Altered Drug Targetsmentioning
confidence: 99%